Hubungan antara Panjang Badan, Lingkar Dada, Lebar Dada, dengan Bobot Badan Babi Duroc Umur Satu Tahun di Mitra Tani Farm Kabupaten Malaka - Bria, Hendrikus Leonito; Kolo, Yuliana; Beyleto, Veronika Y (Tropical Livestock Science Journal, 2025)
Research was carried out at Mitra Tani Farm Malaka for 1 month. The aim of the research was to determine the relationship between body length, chest circumference and chest width on the body weight of one year old Duroc pigs. The materials and methods used were 54 Duroc pigs (14 males, 40 females using the case study method with direct measurements in the field. The tools and materials in this research were measuring sticks, measuring tape, scales, and cameras. This research used case study research methods and direct measurements in the field. The data obtained were analyzed using simple statistics and displayed descriptively. Statistical analysis in this research was descriptive statistics and correlation using SPSS v25. The average body size of male Duroc pigs consists of body length 94.29 ± 3.17 cm, chest circumference 137.36 ± 4.84 cm, chest width 26.57 ± 0.74 cm, and body weight 117.29 ± 4.79 kg, while the average body size of female Duroc pigs is body length 88.80 ± 4.40 cm, chest circumference 150.88 ± 11.68 cm, chest width 26.85 ± 0.44 cm, weight 118.78 ± 4.75 kg. The correlation between body length of males (0.647), females (0.646) show a strong relationship, chest circumference and body weight of males (0.998), females (0.882) show a very strong relationship, and chest width and body weight of males (0.873 strong correlation), females (0.501 moderate correlation), so it can be concluded that chest circumference has a very strong relationship with the body weight of males and females. Body length also shows a strong correlation, while chest width is strongly correlated in males and moderately in females.